2006
DOI: 10.1152/ajpregu.00658.2005
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol improves cardiac and hepatic function after trauma-hemorrhage: role of enhanced heat shock protein expression

Abstract: -Although studies indicate that 17␤-estradiol administration after trauma-hemorrhage (T-H) improves cardiac and hepatic functions, the underlying mechanisms remain unclear. Because the induction of heat shock proteins (HSPs) can protect cardiac and hepatic functions, we hypothesized that these proteins contribute to the salutary effects of estradiol after T-H. To test this hypothesis, male Sprague-Dawley rats (ϳ300 g) underwent laparotomy and hemorrhagic shock (35-40 mmHg for ϳ90 min) followed by resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
1
41
1
Order By: Relevance
“…Our previous studies showed that cardiac output was significantly decreased in the trauma-hemorrhage rats and was restored to normal after E 2 administration following trauma-hemorrhage (11,41). Furthermore, ϩdP/dt max and ϪdP/dt max can reflect the value of cardiac output in sham and trauma-hemorrhage rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous studies showed that cardiac output was significantly decreased in the trauma-hemorrhage rats and was restored to normal after E 2 administration following trauma-hemorrhage (11,41). Furthermore, ϩdP/dt max and ϪdP/dt max can reflect the value of cardiac output in sham and trauma-hemorrhage rats.…”
Section: Discussionmentioning
confidence: 95%
“…HSPs are induced by exposure to a number of different stresses, including heat and ischemia, and they help minimize the damaging effect of such stress on the heart (20,26). Our previous studies showed that administration of 17␤-estradiol (E 2 ) after trauma-hemorrhage restores cardiac function through upregulation of HSP expression (41,45). Furthermore, studies have demonstrated that HSP27 and ␣ B -crystallin are downstream of p38 MAPK (6,8,10).…”
mentioning
confidence: 99%
“…␣-Glutathione S-transferase (␣-GST) is a highly sensitive and specific biomarker of hepatic injury (4,35). At 2 h after resuscitation, plasma samples were obtained.…”
Section: Trauma-hemorrhagic Modelmentioning
confidence: 99%
“…The mechanisms responsible for the gender dimorphic response include differences in proinflammatory cytokine, reactive oxygen species, and vasoregulatory action [16,17]. Our previous studies have shown that administration of female sex steroid hormone, 17b-estradiol (E2) [18,19], or androgen receptor antagonist, flutamide [20], protects hepatic function following trauma-hemorrhage. Furthermore, recent studies have suggested that the salutary effects of E2 on organ function after trauma-hemorrhage are mediated in part via upregulation of Hsps [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that administration of female sex steroid hormone, 17b-estradiol (E2) [18,19], or androgen receptor antagonist, flutamide [20], protects hepatic function following trauma-hemorrhage. Furthermore, recent studies have suggested that the salutary effects of E2 on organ function after trauma-hemorrhage are mediated in part via upregulation of Hsps [18]. There are two estrogen receptors (ERs), ER-a and ER-b, which are differentially expressed in different tissues [21].…”
Section: Introductionmentioning
confidence: 99%